2011
DOI: 10.5047/eps.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Along-dip segmentation of the 2011 off the Pacific coast of Tohoku Earthquake and comparison with other megathrust earthquakes

Abstract: The 11 March 2011 Tohoku Earthquake ruptured the interplate boundary off-shore of east Japan, with fault displacements of up to 40 m and a rupture duration of 150-160 s. W-phase inversion indicates a moment of 3.9 × 1022 N m (Mw 9.0) and a centroid time of 71 s. We invert teleseismic P waves and broadband Rayleigh wave observations with high-rate GPS recordings from Japan to characterize the rupture. The resulting rupture model begins with a steady increase of moment rate for the first 80 s, and a rupture spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Reports on tsunami excitation and seismic waveform inversions of teleseismic and strong motion data (Koketsu et al, 2011;Yoshida et al, 2011) revealed a large fault slip in Segments B and C , supporting the scenario of our strong initial rupture. The lack of strong seismic directivity in the excitation of long-period surface waves (Ide et al, 2011;Yomogida et al, 2011) also supports the contention that the majority of the seismic moment release was concentrated in the initial break of the hypocentral area.…”
Section: The 2011 Tohoku-oki Megathrust Earthquakesupporting
confidence: 57%
See 2 more Smart Citations
“…Reports on tsunami excitation and seismic waveform inversions of teleseismic and strong motion data (Koketsu et al, 2011;Yoshida et al, 2011) revealed a large fault slip in Segments B and C , supporting the scenario of our strong initial rupture. The lack of strong seismic directivity in the excitation of long-period surface waves (Ide et al, 2011;Yomogida et al, 2011) also supports the contention that the majority of the seismic moment release was concentrated in the initial break of the hypocentral area.…”
Section: The 2011 Tohoku-oki Megathrust Earthquakesupporting
confidence: 57%
“…As has been pointed out previously (Yomogida et al, 2011), a prime factor that had not been recognized before is the along-dip double segmentation along the Japan trench, due to the distinction between shallow and deep seismic segments perpendicular to the trench axis, and their successive ruptures induced by the strong initial break of the trench-ward segments. The double segmentation in the Tohoku district is due to the apparent absence of earthquakes, historically, in the trench-ward segments, in contrast to the smaller (up to M w 7.5) earthquakes that repeatedly break the deeper, Japan Island-ward segments.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The 1952 Kamchatka earthquake of Mw 9.0 and the 1964 Alaska earthquake of Mw9.2 are pointed out to be of ADDS type, while the 1960 Chile earthquake of Mw9.5 and the 2010 Maule earthquake of Mw8.8 are of ASSS [4,5]. Speaking about the 2004 Sumatra-Andaman earthquake of Mw9.3, the faulting process is peculiar.…”
Section: Diversity Of Megathrust Earthquakes In the Worldmentioning
confidence: 99%
“…It has been pointed out recently that observations of their seismic activity in recent years revealed that the megathrust earthquakes occurred in seismic segments of either Along-strike Single Segmentation (ASSS) or Along-dip Double Segmentation (ADDS) [4][5][6]. The different seismic segmentations-ASSS and ADDS-have been identified, referring to their regional seismic-activity, focal mechanisms, rupture patterns, geometry of subduction zones, types of overriding plates and back-arc activity [5].…”
Section: Introductionmentioning
confidence: 99%